Alzheimer's Prevention Initiative Generation Program: Development of an APOE genetic counseling and disclosure process in the context of clinical trials - Carolyn M. Langlois; Angela Bradbury; Elisabeth M. Wood; J. Scott Roberts; Scott Y.H. Kim; Marie‐Emmanuelle Riviere; Fonda Liu; Eric M. Reiman; Pierre N. Tariot; Jason Karlawish; Jessica B. Langbaum (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction As the number of Alzheimer's disease (AD) prevention studies grows, many individuals will need to learn their genetic and/or biomarker risk for the disease to determine trial eligibility. An alternative to traditional models of genetic counseling and disclosure is needed to provide comprehensive standardized counseling and disclosure of apolipoprotein E (APOE) results efficiently, safely, and effectively in the context of AD prevention trials. Methods A multidisciplinary Genetic Testing, Counseling, and Disclosure Committee was established and charged with operationalizing the Alzheimer's Prevention Initiative (API) Genetic Counseling and Disclosure Process for use in the API Generation Program trials. The objective was to provide consistent information to research participants before and during the APOE counseling and disclosure session using standardized educational and session materials. Results The Genetic Testing, Counseling, and Disclosure Committee created a process consisting of eight components: requirements of APOE testing and reports, psychological readiness assessment, determination of AD risk estimates, guidance for identifying providers of disclosure, predisclosure education, APOE counseling and disclosure session materials, APOE counseling and disclosure session flow, and assessing APOE disclosure impact. Discussion The API Genetic Counseling and Disclosure Process provides a framework for large‐scale disclosure of APOE genotype results to study participants and serves as a model for disclosure of biomarker results. The process provides education to participants about the meaning and implication(s) of their APOE results while also incorporating a comprehensive assessment of disclosure impact. Data assessing participant safety and psychological well‐being before and after APOE disclosure are still being collected and will be presented in a future publication.